2022
DOI: 10.3390/ijms23052845
|View full text |Cite
|
Sign up to set email alerts
|

Protoplast Dissociation and Transcriptome Analysis Provides Insights to Salt Stress Response in Cotton

Abstract: As one of the pioneer crops widely planted in saline-alkaline areas, Gossypium provides daily necessities, including natural fiber, vegetable proteins, and edible oils. However, cotton fiber yield and quality are highly influenced by salt stress. Therefore, elucidating the molecular mechanisms of cotton in response to salinity stress is importance to breed new cultivars with high tolerance. In this study, we first developed a method for single-cell RNA-seq based on isolating protoplast from cotton root tips; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…For example, root age influences the quantity and quality of protoplasts. Liu [ 12 ] compared the yield and viability of protoplasts isolated from 5-, 7-, 9- and 10-day-old root tips. They found that 5-day-old root-generated protoplasts exhibited high viability (~ 85%) and were suitable for transcriptome sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, root age influences the quantity and quality of protoplasts. Liu [ 12 ] compared the yield and viability of protoplasts isolated from 5-, 7-, 9- and 10-day-old root tips. They found that 5-day-old root-generated protoplasts exhibited high viability (~ 85%) and were suitable for transcriptome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental stage of the materials used is critical for successful protoplast isolation [ 12 ]. During seed germination, the radicle breaks through the seed coat to form a primary root and begin primary growth.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have been conducted on cotton based on its salt tolerance ability by utilizing quantitative trait loci (QTL) by linkage mapping and genome-wide association studies. Little work on the transcriptomic and metabolomic aspects has been conducted yet [56][57][58]. Several QTL or genes were discovered by scientists in previous studies on the salt tolerance mechanism of cotton [55,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that they also revealed that external stimuli, such as sucrose, can influence the developmental process, causing changes in sucrose response-related cells. In a similar case, in 2022, a group studied another external stimulus, salt stress, using cotton as their object and observed the influence of external stimuli on the profile and dynamic changes in gene expression ( Liu et al., 2022b ). For further research on the exploration of cellular heterogeneity, it is essential to compare gene expression profiles before and after external environmental stimuli by studying single-cell transcriptome sequencing results and constructing an atlas.…”
Section: Development Of Plant Single-cell Transcriptomicsmentioning
confidence: 99%